2021
DOI: 10.1073/pnas.2100099118
|View full text |Cite
|
Sign up to set email alerts
|

Physical theory of biological noise buffering by multicomponent phase separation

Abstract: Maintaining homeostasis is a fundamental characteristic of living systems. In cells, this is contributed to by the assembly of biochemically distinct organelles, many of which are not membrane bound but form by the physical process of liquid–liquid phase separation (LLPS). By analogy with LLPS in binary solutions, cellular LLPS was hypothesized to contribute to homeostasis by facilitating “concentration buffering,” which renders the local protein concentration within the organelle robust to global variations i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 59 publications
6
60
0
Order By: Relevance
“…Adding another type of solute into the system leads to drastically richer phase behaviors, as hinted by a ternary regular solution model ( Deviri and Safran, 2021 ; Dignon et al, 2020 ; Meijering, 1950 ). With additional components in the system, the phase diagram now incorporates another axis for the concentration of the second solute, and becomes three-dimensional ( Fig.…”
Section: Rich Phase Behaviors Of Ternary Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding another type of solute into the system leads to drastically richer phase behaviors, as hinted by a ternary regular solution model ( Deviri and Safran, 2021 ; Dignon et al, 2020 ; Meijering, 1950 ). With additional components in the system, the phase diagram now incorporates another axis for the concentration of the second solute, and becomes three-dimensional ( Fig.…”
Section: Rich Phase Behaviors Of Ternary Systemsmentioning
confidence: 99%
“…The ternary model also provides important insights regarding the noise buffering effect of phase separation. Unlike the simple buffering effect in the binary system discussed above ( Klosin et al, 2020 ), the degree of noise buffering in the ternary system varies significantly depending on the type of phase diagrams and the orientation of concentration variability imposed on the system ( Deviri and Safran, 2021 ). Indeed, recent work experimentally demonstrated that the dilute-phase concentrations of intracellular condensates are often not fixed but rather increase as the expression of protein components increases ( Riback et al, 2020 ).…”
Section: Rich Phase Behaviors Of Ternary Systemsmentioning
confidence: 99%
“…This allows for richer behavior, thus giving a better picture of real systems. In fact, even equilibrium phase separation is already complex in ternary systems since now many phases with different compositions may form [28,69,70].…”
Section: Ternary Fluid With a Conversion Reactionmentioning
confidence: 99%
“…However, experimentally relevant systems, and in particular biological examples, typically contain many more interacting components [75]. In fact, even ternary mixtures can display surprisingly complex phase diagram [34,69,70,76] and this trend continuous for increasing component counts [28,77]. We can now simulate systems of a few tens of components [42,43] and analyze large systems in particular cases using random matrix theory [42,[78][79][80] and scaling analysis [81].…”
Section: Multi-component Fluids and Complex Reactionsmentioning
confidence: 99%
“…(1) Biomolecular condensates (BC) appear in numerous locations in cells where they carry out many biochemical functions. (2, 3) They modulate enzymatic activity,(4-7), a function that has been reproduced with rationally designed peptides;(8-10) buffer protein concentration,(11) reduce noise in gene expression,(12) and regulate cell migration. (13) Phase separation of IDPs is crucial for the healthy functioning of neuronal synapses in the presynaptic axon(14, 15) and postsynaptic dendrite.…”
Section: Introductionmentioning
confidence: 99%